PP150 Bevan Health Technology Exemplars: Early Dialogue To Systematize HTA. (2019) - Myles, Susan; Charles, Sion; Davies, Claire; Elston, Lauren; Howson, Helen; Poole, Ruth Louise
Abstract : Introduction: Wales has ambitious health, wealth, and innovation policies and a clear goal to use the economic muscle of the Welsh National Health Service (NHS) to support its strong life sciences sector. Health Technology Wales (HTW) has a clear remit to appraise technologies over the span of their lifecycle from innovation to obsolescence. HTW is collaborating with the Bevan Commission through their national Health Technology Exemplars (HTEs), which partners NHS and industry stakeholders to strengthen innovation within the Welsh health system. Methods: Health technology assessment (HTA) methods were used to produce topic exploration reports for assessing the evidence underpinning applicant innovations. A "Dragons' Den" expert panel was convened to select the successful HTEs. Results: Fourteen Bevan HTEs were awarded funds, which were matched by industry partners. Application of HTA methods resulted in more critical consideration of technology value propositions, including: developing pull models of innovation focused on delivering health technology solutions for current problems facing NHS Wales; supporting early dialogue between the NHS and industry partners around demonstrating evidence of improved patient outcomes; and focusing on transformative rather than incremental innovation. The most promising innovations will progress to rapid HTA, where the evidence generated will be used to develop guidance for NHS Wales. Conclusions: HTA methods were productively deployed at the innovation phase of the technology lifecycle to support evidence-informed allocation of scarce innovation resources. In this way, HTW is working with key stakeholders to identify and offer early support to the most promising innovations, with the aim of expediting their adoption and realizing health benefits for patients as quickly as possible. The Bevan Commission has partnered with HTW to routinely build in HTA and evidence considerations in its future innovation calls and competitions. Thus, HTW has established a "feeder" pipeline for assessing bottom-up service-led innovations and encouraging evidence consideration throughout the lifecycle of innovative technologies.